Flood fatalities in Athens, Greece: 1880- 2010. - Diakakis, M.; Katsetsiadou, K.; Pallikarakis, A. (Bulletin of the Geological Society of Greece, 2013)
Flood-related deaths in urban environments constitute a major issue in flood risk management especially during the last decades, as global urban population grows larger. This work focuses on the analysis of flood-related fatalities in Athens metropolitan area, in Greece between 1880 and 2010. To this aim, a database is compiled, recording spatial and temporal distribution of fatal flood incidents, along with demographic information on the victims. GIS is used to map and spatially analyze the incidents in question and to examine possible migration trends. Results showed a total of 182 fatalities across Athens basin, presenting a decreasing trend, even though flood event numbers are rising. Males, youngsters and elderly people showed an overrepresentation amongst the victims in comparison with the country’s general population. Fatal incidents presented a higher spatial density in the central and southwestern parts of the city indicating a higher persistence of flood phenomena in these areas. A gradual migration of fatality locations, from the central parts of the city, towards the outer suburbs during the study period was identified following the city’s spatial expansion.